Kekuatan Hukum Akta Penegasan Untuk Tindakan Daluwarsa Pendaftaran Akta Jaminan Fidusia - Dinda Prasetiani, Norika; Putrijanti, Aju (UNES Law Review, 2024)
The fiduciary guarantee deed must be registered inaccordance with applicable laws and regulations within 30 (thirty) days after the deed is drawn up. However,there are times when the fiduciary deed is registered late by the notary or the parties. To overcome this delay, the notary makes a deed of confirmation to re-register the fiduciary guarantee deed that is registered too late. This study uses a type of normative legal research, using a statutory approach. The normative juridical approach is carried out by examining various formal legal rules such as laws, regulations, and literature that contains theoretical concepts related to the topic and problem of this research. The results of this study indicate that the validity of the affirmation deed made before a notary public due to the expiration date of the registration of the fiduciary deed is legally valid, but the existence of the affirmation deed cannot replace the position of the fiduciary deed because the contents of the affirmation deed and the fiduciary deed are very different. Delay in registeringthe deed has implications for defects in the fiduciary guarantee deed,making a new deed would be better done than using an affirmation deed that has no legal basis in the law. An affirmation deed made for a fiduciary guarantee that is registered too latecannot provide legal protection to the parties because a deed that is registered too late does not have an executorial title. The deed of confirmation of a fiduciary guarantee appears to accommodate a deed of fiduciary security that has passed the registration deadline. The technique for making a deed of confirmation of a fiduciary guarantee is still made before a notary and in the premise of the deed it is stated that a fiduciary deed has not previously been registered.